Impact of Clear, Loud, and Slow Speech on Scaled Intelligibility and Speech Severity in Parkinson’s Disease and Multiple Sclerosis - Tjaden, Kris (J Speech Lang Hear Res, 2014)
PURPOSE: The perceptual consequences of rate reduction, increased vocal intensity, and clear speech were studied in speakers with multiple sclerosis (MS), Parkinson’s disease (PD), and healthy controls. METHOD: Seventy-eight speakers read sentences in habitual, clear, loud, and slow conditions. Sentences were equated for peak amplitude and mixed with multitalker babble for presentation to listeners. Using a computerized visual analog scale, listeners judged intelligibility or speech severity as operationally defined in Sussman and Tjaden (2012). RESULTS: Loud and clear but not slow conditions improved intelligibility relative to the habitual condition. With the exception of the loud condition for the PD group, speech severity did not improve above habitual and was reduced relative to habitual in some instances. Intelligibility and speech severity were strongly related, but relationships for disordered speakers were weaker in clear and slow conditions versus habitual. CONCLUSIONS: Both clear and loud speech show promise for improving intelligibility and maintaining or improving speech severity in multitalker babble for speakers with mild dysarthria secondary to MS or PD, at least as these perceptual constructs were defined and measured in this study. Although scaled intelligibility and speech severity overlap, the metrics further appear to have some separate value in documenting treatment-related speech changes.